Rhizoctonia solani AG-3PT is the major pathogen associated with potato stem canker and black scurf in Colombia - Johan Manuel Cifuentes (Agronomía Colombiana, 2012)
Stem canker and black scurf diseases of potatoes are caused by the basidiomycetous fungus Thanatephorus cucumeris (anamorphic species complex Rhizoctonia solani). These diseaseshave worldwide distribution wherever potato is grown but their etiology varies depending on the predominance of distinct R. solani anastomosis groups (AGs) in a particular area. Within the species complex, several AGs have been associated with stem canker or black scurf diseases, including AG-1, AG-2-1, AG-2-2, AG-3, AG-4, AG-5 and AG-9. This article reports on the most comprehensive population-based study, providing evidence on the distribution of R. solani AGs in Colombian potato fields. A total of 433 isolates were sampled from the main potato cropping areas in Colombia from 2005 to 2009. Isolates were assigned to AGs by conventional PCR assays using specific primers for AG-3, sequencing of the ITS-rDNA and hyphal interactions. Most of the isolates evaluated were assigned to AG-3PT (88.45%), and a few to AG-2-1 (2.54%). The remaining isolates were binucleate Rhizoctonia (AG-A, E, and I). Pathogenicity tests on the stems and roots of different plant species, including the potato, showed that AG-3PT affects the stems of solanaceous plants. In other plant species, damage was severe in the roots, but not the stems. AG-2-1 caused stem canker of Solanum tuberosum cv. Capiro and in R. raphanistrum and B. campestris subsp. Rapa plantlets and root rot in other plants. The results of our study indicated that R. solani AG-3PT was the principal pathogen associated with potato stem canker and black scurf diseases of potatoes in Colombia.